Muhammad as an episcopal figure - Sinai, N (Brill Academic Publishers, 2018)
The Medinan stratum of the Qurʾān ascribes to Muḥammad a noticeably elevated status and a far wider range of functions than the earlier Meccan layer. Although this shift may well have responded to, and been facilitated by, historical circumstances, it is nonetheless appropriate to inquire whether specific aspects of it might be drawing on pre-Qurʾānic precedents. I argue that the Christian episcopate, arguably the most widespread type of urban religious leadership in late antiquity, yields a surprising number of close overlaps with the Medinan presentation of the function and authority of Muḥammad. In tandem with this assessment, however, the article also considers important differences between the figure of Muḥammad and that of the Christian bishop. The most important such divergence consists in the fact that the Qurʾānic Messenger, unlike a Christian bishop, does not owe his authority to ordination by an ecclesiastical hierarchy: Muḥammad does not occupy an office that imparts authority independently of the person occupying it.